Disturbance Rejection Based Current Control for Permanent Magnet Synchronous Motor Drives Using a Discrete-Time Adaptive Controller With Periodic Estimation - Kaya, Ramazan; Adiguzel, Fatih (WILEY, 2025)
In this paper, a non-linear adaptive direct current controller based on periodic estimation is proposed to significantly minimize the periodic torque ripples for the permanent-magnet synchronous motor system in the discrete-time setting. The discrete-time adaptive controller is designed to track the desired motor currents of motor and provide periodic disturbance rejection by constructing the estimation algorithm based on the digital processing of unknown periodic signals in each consecutive motor period, which requires only knowledge of periodicity. The asymptotic stability of the closed-loop system dynamics is proven through the convergence of current errors to zero as the period of the motor shaft approaches infinity. To test the robustness against periodic uncertainties and disturbances varying with the rotor displacement and to demonstrate the achievement of the desired steady-state response for stator current quality, detailed simulation experiments are carried out with comparisons to the classical deadbeat controller.
Keywords: discrete-time control; disturbance rejection; periodic adaptation; permanent magnet synchronous motor drive; TORQUE RIPPLE MINIMIZATION; CURRENT-CONTROL SCHEME; PREDICTIVE CURRENT CONTROL; VARYING PARAMETERS; PMSM; SUPPRESSION; MODEL; IMPLEMENTATION; DESIGN; SPEED; Automation & Control Systems; Engineering